Lead with wisdom : how wisdom transforms good leaders into great leaders - Strom, Mark, 1956- (Wiley, 2014)
A practical guide for leading others with wisdom, integrity, and humanity This book argues that great leadership requires wisdom. Rather than a formulaic managerial approach to leadership, Lead with Wisdom presents the case for leadership based on our shared humanity and the stories that unite us. What emerges is a model of leadership based on learning to read key patterns of human experience: the way language shapes our reality, how we form new meaning through conversation, how relationships determine influence and how we deal with uncertainty. It presents readers with the tools and illustra.